Anti-biofilm activity: a function of Klebsiella pneumoniae capsular polysaccharide. - Marina Dos Santos Goncalves (Public Library of Science (PLoS), 2014)
Competition and cooperation phenomena occur within highly interactive biofilm communities and several non-biocides molecules produced by microorganisms have been described as impairing biofilm formation. In this study, we investigated the anti-biofilm capacities of an ubiquitous and biofilm producing bacterium, Klebsiella pneumoniae. Cell-free supernatant from K. pneumoniae planktonic cultures showed anti-biofilm effects on most Gram positive bacteria tested but also encompassed some Gram negative bacilli. The anti-biofilm non-bactericidal activity was further investigated on Staphylococcus epidermidis, by determining the biofilm biomass, microscopic observations and agglutination measurement through a magnetic bead-mediated agglutination test. Cell-free extracts from K. pneumoniae biofilm (supernatant and acellular matrix) also showed an influence, although to a lesser extend. Chemical analyses indicated that the active molecule was a high molecular weight polysaccharide composed of five monosaccharides: galactose, glucose, rhamnose, glucuronic acid and glucosamine and the main following sugar linkage residues [→ 2)-α-L-Rhap-(1 →]; [→ 4)-α-L-Rhap-(1 →]; [α-D-Galp-(1 →]; [→ 2,3)-α-D-Galp-(1 →]; [→ 3)-β-D-Galp-(1 →] and, [→ 4)-β-D-GlcAp-(1 →]. Characterization of this molecule indicated that this component was more likely capsular polysaccharide (CPS) and precoating of abiotic surfaces with CPS extracts from different serotypes impaired the bacteria-surface interactions. Thus the CPS of Klebsiella would exhibit a pleiotropic activity during biofilm formation, both stimulating the initial adhesion and maturation steps as previously described, but also repelling potential competitors.